The railway children - Morshead, Catherine; Nye, Simon, 1958-; Agutter, Jenny; Fisher, Gregor; Attenborough, Richard; Lacey, Simon; Nesbit, E. 1858-1924 (Edith); Carlton Television; WGBH Video (Firm) ([South Burlington, VT] : WGBH Video, 2002)
Three children befriend local train travelers as they try to learn what has become of their missing father.
Based on the novel by Edith Nesbit.
Director of photography, John Daly ; production design, Tim Hutchinson ; editor, Don Fairservice ; music, Simon Lacey.
Jenny Agutter, Gregor Fisher, Richard Attenborough, Michael Kitchen, Jemima Rooper.
Originally broadcast on Masterpiece Theatre.
Not rated.
DVD Dolby digital.
Keywords: Nesbit, E. -- 1858-1924 -- Film and video adaptations; Families -- England -- Drama; Brothers and sisters -- Drama; Railroads -- England -- Drama; Country life -- England -- Drama; Video recordings for hard of hearing people; Based on the book; Feature films